Management Style of Business Organization Leaders in Indonesia: A Mixed Study - Widia Sri Ardias; Bagus Riyono; Sumaryono Sumaryono; Edilburga Wulan Septandari; Rifa Juniartika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Leadership is crucial element in the pursuit of organizational objectives. The examination of the characteristics of a proficient leader remains a compelling area of research, given its perceived capability to address diverse challenges, particularly those related to the organizational systems and human resources. This research used a convergent parallel mix-method to reveal type and profile of organizational management style that are effectively applied in business organizations in Indonesia today. Quantitative results revealed that the majority of managers in Indonesia apply a basic leadership separation (separated) style because of the lack of task orientation and relationships, which when affective produce a managerial style bereaucrate and when ineffective apply a deserter style. Temporary results qualitatively showed that at least four dimensions assessed must be owned by one person's leader: capacity to think strategically (strategic thinking), skilled management of tasks (task management), professional, and capable manage people or teams (people management). Integration results found convergent data because there are suitability dimensions between quantitative data and qualitative data related to management tasks and human management. Furthermore, it also obtained the results of the expansion from qualitative data was the emergence of the theme of strategic and professional thinking as a dimension that must be possessed by an effective leader in business organizations. Implications obtained based on the integration of quantitative and qualitative data analysis are perceptions that the profile ideal and effective leader can differ from what an individual applies inside the organization. As a result, even if the manager recognizes what capacities a leader should have, in practice, he may apply different styles and approaches.